The Impact of 6-Degree Lateral Wedge Insoles on Pain, Functional Parameters, and adduction Moment in Patients with Knee Osteoarthritis: A Six-Week Randomized Controlled Trial - Jamehbozorgi, Ali asghar; Rezaei, Mehdi (Journal of Clinical Physiotherapy Research, 2023)
Knee osteoarthritis (OA) is a prevalent degenerative joint disease that significantly impacts physical function and quality of life. While traditional management strategies focus on pharmacological and surgical interventions, the role of footwear modifications, such as lateral wedge insoles, has gained attention. This study aimed to investigate the effects of 6-degree lateral wedge insoles on pain, functional outcomes, and biomechanical parameters, such as the adductor moment, in patients with knee OA over six weeks. This was a randomized clinical trial study that twenty-one participants aged 50–75 years with moderate to severe knee OA were randomized into an intervention group (n=11), which received 6-degree lateral wedge insoles, and a control group (n=10), which used flat insoles. Pain levels, functional performance, and adductor moment were assessed at baseline and after six weeks. Results showed significant improvements in pain (45% reduction, P=0.003) and joint stiffness (30% reduction, P=0.001) in the intervention group, along with a 13% reduction in the adductor moment (P=0.021). Immediate effects also demonstrated a 35% reduction in pain (P=0.007) and a 42% reduction in stiffness (P=0.001). These findings suggest that 6-degree lateral wedge insoles can provide both immediate and sustained benefits for knee OA patients, highlighting their potential as a non-invasive management strategy.